Perfil fenotípico e de expressão de proteínas de Cryptococcus neoformans após tratamento com substâncias obtidas da planta Pterogyne nitens - Leite, Fernanda Sangalli [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
A criptococose tem emergido como importante infecção oportunista em pacientes imunossuprimidos e imunocompetentes causando principalmente a neurocriptococose. Cryptococcus neoformans, um dos agentes, é uma levedura capsulada comumente encontrada em infecções do sistema nervoso central em pacientes HIV positivos. No mercado há fármacos para o tratamento dessas infecções, porém problemas são verificados quanto ao espectro de ação, custos e efeitos adversos. As plantas são usadas na medicina por longa data constituindo-se de uma ótima alternativa para busca de substâncias que podem ser utilizadas na formulação de novos antifúngicos. Neste estudo foram avaliados vários extratos, frações e substâncias puras do projeto BIOTA frente à cepa ATCC de C. neoformans, bem como em isolados clínicos com perfil de sensível e resistente frente ao fluconazol. Também foi feita a padronização e aplicação da metodologia do “tabuleiro de xadrez” para verificação de atividade sinérgica, aditiva, indiferente e antagônica entre as frações de plantas de interesse, bem como a molécula pedalitina associada com outras substâncias de origem vegetal e com as drogas sintéticas fluconazol e anfotericina B. Os que apresentaram melhores concentrações inibitórias mínimas...

Cryptococcosis is a disease that has emerged as an important opportunistic infection in immunocompromised and immunocompetent patients mainly causing cryptococcal meningitis. Cryptococcus neoformans, one of the agents, is encapsulated yeast most commonly found in central nervous system infections in HIV patients. There are drugs on the marketplace for the treatment of these infections, but problems are related to spectrum of action, costs and adverse effects. Plants are used in medicine for a long time and they are a great alternative to look for substances that can be used to develop new antifungal agents. In this study we evaluated several extracts, fractions and pure substances from BIOTA project against the ATCC strain of C. neoformans, as well as clinical isolates with sensible and resistant profile to fluconazole. The standardization and application of the methodology of the chessboard technique was developed to verify synergistic, additive, indifferent and antagonistic activities among the fractions of the selected plants, and the molecule pedalitin associated with other natural compounds and the synthetic drugs fluconazole and amphotericin B. The substances that presented the best minimum inhibitory concentrations were selected to verify the fungi protein profile before and after contact with the plant substance and adhesion profile to cells (pneumocytes) A549. Among the plants studied, Pterogyne nitens, specie that belongs to the family Fabaceae, which has the active substance called pedalitin, presented a significant antifungal activity against the isolates of C. neoformans including resistant. Suspensions of C. neoformans with and without treatment with fluconazole and in contact with pedalitin were analyzed by SDS-PAGE and two-dimensional electrophoresis. These treatments revealed changes in the expression... (Complete abstract click electronic access below)
Keywords: Atividade antifúngica; Crypotococcus neoformans; Antifungal agents; Cryptococcosis; Cryptococcus neoformans